The Feasibility of Texture-based Quantification for Evaluating Lumbar Intervertebral Disc Degeneration in Adolescent Idiopathic Scoliosis from Conventional T2-weighted Magnetic Resonance Imaging - Fengxian WANG; Shoufeng WANG; Ying CHANG; Jin ZHOU; Jing CHEN; Zhengyang ZHOU; Dongmei WANG (CT Lilun yu yingyong yanjiu, 2023)
Objective: To investigate the utility of texture data based on T2-weighted magnetic resonance imaging (MRI) in determining intervertebral disc degeneration in adolescent idiopathic scoliosis (AIS). Materials and Methods：From October 2016 and March 2020, 122 patients with AIS and 40 volunteers who underwent 3.0T MRI were prospectively included. The following MRI texture data were generated: (1) mean, (2) standard deviation, (3) max, (4) min, (5) the fifth, 10th, 25th, 50th, 75th and 90th percentiles; (6) skewness; (7) kurtosis; and (8) entropy. The Pfirrmann system was used to evaluate the intervertebral discs of all participants. Patients with Pm I were divided into groups 1 and 2. Volunteers were classified into 0. Differences and correlations between the groups were analyzed. Results: The mean, standard deviation, max, entropy and the 5th, 10th, 25th, 50th, 75th, and 90th percentiles in group 2 were significantly lower than those in group 1 and group 0; the min in group 2 was significantly lower than in group 0; the skewness in group 2 was significantly higher than in group 1 and group 0; the kurtosis in group 2 was significantly lower than in group 1; the skewness in group 1 was significantly higher than in group 0 and the standard deviation, min, kurtosis and 5th, 10th, 25th, and 50th percentiles in group 1 were significantly lower than those in group 0. Conclusion: Texture analysis can be used to assess early degenerative changes in the intervertebral discs of patients with AIS.